Optical solitons with M-truncated derivative and conservation laws for NLSE equation which describe pseudospherical surfaces - Yusuf, Abdullahi; İnç, Mustafa (Iop Publishing Ltd, 2020)
The present work analyzes the optical solitons with M-truncated and conservation laws (Cls) of the nonlinear Schrodinger equation that explain pseudospherical surfaces. The well-known integration scheme which is generalized Bernoulli sub-ODE method is utilized to construct such optical soliton solutions. For the successful existence of the solutions, the constraints conditions have been presented. The discussion for the physical features of the obtained solutions is reported. Moreover, we establish Cls for the equation under consideration by means of multiplier approach.
Keywords: generalized Bernoulli sub-ODE method; M-truncated derivative; optical solitons